Effect of exercise training on weight loss, body composition changes, and weight maintenance in adults with overweight or obesity: An overview of 12 systematic reviews and 149 studies. (6th May 2021) - Bellicha, Alice; van Baak, Marleen A.; Battista, Francesca; Beaulieu, Kristine; Blundell, John E.; Busetto, Luca; Carraça, Eliana V.; Dicker, Dror; Encantado, Jorge; Ermolao, Andrea; Farpour‐Lambert, Nathalie; Pramono, Adriyan; et al.
Summary: This overview of reviews aimed to summarize the effects of exercise training programs on weight loss, changes in body composition, and weight maintenance in adults with overweight or obesity. A systematic search of systematic reviews and meta‐analyses (SR‐MAs) published between 2010 and December 2019 was performed. Only SR‐MAs of controlled trials were included. The mean difference (MD) or standardized MD (SMD) were extracted from SR‐MAs. Twelve SR‐MAs (149 studies) were included. Exercise led to a significant weight loss (4 SR‐MAs, MDs ranging from −1.5 to −3.5 kg), fat loss (4 SR‐MAs, MDs ranging from −1.3 to −2.6 kg) and visceral fat loss (3 SR‐MAs, SMDs ranging from −0.33 to −0.56). No difference in weight, fat, and visceral loss was found between aerobic and high‐intensity interval training as long as energy expenditure was equal. Resistance training reduced lean mass loss during weight loss (1 SR‐MA, MD: 0.8 [95%CI: 0.4–1.3] kg). No significant effect of exercise was found on weight maintenance (1 SR‐MA). These findings show favorable effects of exercise training on weight loss and body composition changes in adults with overweight or obesity. Visceral fat loss may lead to benefits for cardiometabolic health. More research is needed to identify training modalities that promote weight maintenance.